Internal training load monitoring in professional football: a systematic review of methods using rating of perceived exertion - Rago, V.; Brito, J.; Figueiredo, P.; Costa, J.; Krustrup, P.; Rebelo, A. (The Journal of Sports Medicine and Physical Fitness, 2020)
INTRODUCTION: The rate of perceived exertion (RPE) is widely adopted to quantify internal training load (ITL) in professional football. The aim of this study was to systematically review the use RPE-based methods in professional football. EVIDENCE ACQUISITION: Observational studies conducted during training routines of professional football players over a minimum of one-week were selected based on the preferred reporting items for systematic reviews and meta-analyses statement. EVIDENCE SYNTHESIS: Thirty-eight articles met the inclusion criteria (average qualitative score was 6.3 out of 10 [3 to 9]). The main deficiencies identified concerned the poor description of study design (~52% of the studies), and the non-quantification of match load (~44%). Ten studies complemented RPE-based ITL information with time-motion analysis (~26%) and seven studies added HR recordings (~18%). Nine studies collected RPE data after complementary training, separately to field sessions (~3%). Operational questions (e.g. How was your workout? ~71%) were preferred to instructions (e.g. Please rate the intensity of today`s session; ~8%). Session-RPE (s-RPE; RPE multiplied by training duration) was more commonly adopted as measure of exercise intensity than isolated RPE (~76 vs. ~8%). RPE-derived variables calculated on weekly values included absolute week-to-week change, acute: chronic workload ratio, monotony and strain and were not frequently used (7 to 15%). Four studies (~11%) divided RPE in two components: respiratory and muscular. CONCLUSIONS: There is a lack of consensus for the use of RPE in professional football and "good practices" are warranted. This review might help practitioners regarding procedures to adopt in RPE data collection and interpretation.